2022
DOI: 10.1002/advs.202202263
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Size of Large Dense‐Core Vesicles and Quantal Neurotransmitter Release via Secretogranin II Liquid–Liquid Phase Separation

Abstract: Large dense‐core vesicles (LDCVs) are larger in volume than synaptic vesicles, and are filled with multiple neuropeptides, hormones, and neurotransmitters that participate in various physiological processes. However, little is known about the mechanism determining the size of LDCVs. Here, it is reported that secretogranin II (SgII), a vesicle matrix protein, contributes to LDCV size regulation through its liquid–liquid phase separation in neuroendocrine cells. First, SgII undergoes pH‐dependent polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 99 publications
0
28
0
Order By: Relevance
“…We observed an increase in the mRNA and protein level of ATF4 in the ER-stressed cells, which reverted towards control levels upon DHA co-treatment (Fig. 8D, 8E Furthermore, experiments on the specificity of altered abundances for other molecular players, such as key SNARES, tethers and rabs, were also tested without significant differences (Supp ER, stress lowers the abundance of key granulogenic signatures: Given the welldocumented evidence about the granulogenic potential of chromogranins, specifically Secretogranin II (SCGII) and Chromogranin A (CGA) (Kim et al, 2001;Lin et al, 2022), we wanted to test if there are any significant changes in the relative abundances of chromogranins in ER-stressed cells. Interestingly, CGA levels were significantly decreased at the mRNA and protein levels, which surprisingly remained unchanged in DHA co-treated cells (Fig.…”
Section: Dha Reverses Impediment To Regulated Secretion In Slvsmentioning
confidence: 99%
“…We observed an increase in the mRNA and protein level of ATF4 in the ER-stressed cells, which reverted towards control levels upon DHA co-treatment (Fig. 8D, 8E Furthermore, experiments on the specificity of altered abundances for other molecular players, such as key SNARES, tethers and rabs, were also tested without significant differences (Supp ER, stress lowers the abundance of key granulogenic signatures: Given the welldocumented evidence about the granulogenic potential of chromogranins, specifically Secretogranin II (SCGII) and Chromogranin A (CGA) (Kim et al, 2001;Lin et al, 2022), we wanted to test if there are any significant changes in the relative abundances of chromogranins in ER-stressed cells. Interestingly, CGA levels were significantly decreased at the mRNA and protein levels, which surprisingly remained unchanged in DHA co-treated cells (Fig.…”
Section: Dha Reverses Impediment To Regulated Secretion In Slvsmentioning
confidence: 99%
“…The LLPS of synapsin I has been demonstrated to form tight clusters of SVs at synapse, resembling dense structures [16] . Recent studies have also shown that DCV matrix proteins CgA, CgB and SgII undergo LLPS, which contributes to vesicular cargo package and vesicle volume determination [1, 2] . These collective findings strongly support the significance of LLPS in biological processes and its association with dense-like features observed under TEM.…”
Section: Introductionmentioning
confidence: 99%
“…Secretogranin III (SgIII), another member in chromogranin family, has been proved to dissolve SgII-mediated LLPS in vitro and reduce the volume of DCVs in native ACCs through overexpression ( Fig. 1D ) [2] . Moreover, using CFE recording, we observed that the reduction in DCV volume caused by SgIII overexpression leads to a reduction in ACC quantal size [2] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations